Intuitionistic Fuzzy Set Based Task Scheduling with QoS Preference Awareness - Juan Wang (Institute of Advanced Engineering and Science, 2014)
Existing task scheduling algorithms in cloud computing lack the ability to be aware of users' quality of service(QoS) preference. In order to address this problem,